(untitled) (Eurasian Research Bulletin, 2023)
Alimentary iron deficiency plays an important role in the development of anemia in preschool children. Milk and muffins often predominate in the diet of children, meat products, vegetables and fruits are limited. An increase in the number of anemia in children is associated with acceleration, higher rates of growth and body weight at birth, as well as with an early doubling of body weight, which is associated with an increase in the need for iron, and hence with the rapid use of endogenous reserves of it. When analyzing the causes of severe iron deficiency anemia, a common one was revealed - drinking about 1-1.5 liters of milk or kefir per day and practically no other food for a month or more. It is clear that this contributes to the development of iron deficiency in the body of children. Thus, it is important to understand that it is necessary to organize a balanced nutrition of the child for all ingredients, including iron